Progressive Multiple Mononeuropathy in a Patient With Familial Transthyretin Amyloidosis After Liver Transplantation. Issue 3 (March 2022) - Seibert, Kaitlin; Wlodarski, Richard; Sarswat, Nitasha; Appelbaum, Daniel; Issa, Naoum P.; Soliven, Betty; Rezania, Kourosh
Abstract : Abstract: Valine 122 isoleucine (V122I) is the most common mutation associated with familial transthyretin-related amyloidosis (fATTR) in the metropolitan United States. V122I-related fATTR usually presents with cardiomyopathy. When polyneuropathy is encountered, it is usually mild, distal, and axonal in nature. Although liver transplantation improves survival for fATTR neuropathy patients, neuropathy may progress post liver transplantation because of the deposition of wild-type transthyretin. We report a patient with homozygous V122I mutation who presented with asymmetrical, upper limb predominant neuropathy rather early in his disease course, which progressed for a period of 5 years after liver transplantation before stabilization with the initiation of patisiran.